2014
DOI: 10.17221/89/2014-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific PCR detection of sweet cherry self-incompatibility alleles S<sub>3</sub>, S<sub>4</sub> and S<sub>9</sub> using consensus and allele-specific primers in the Czech Republic

Abstract: Sharma K., Sedlák P., Zeka D., Vejl P., Soukup J., 2014. Allele-specific PCR detection of sweet cherry selfincompatibility alleles S 3 , S 4 and S 9 using consensus and allele-specific primers in the Czech Republic. Hort. Sci. (Prague), 41: 153-159.Prunus avium species of the Rosaceae family exhibit gametophytic self-incompatibility. Determination of the selfincompatibility genotype of individuals is essential for genetic studies and the development of informed management strategies. The PCR-based detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
(38 reference statements)
2
8
0
Order By: Relevance
“…Normal pollen tube growth was observed in varieties 'Lapins' and 'Staccato,' which agreed with their self-compatible S4 0 haplotype (Schuster, 2012;Sharma, Sedl ak, Zeka, Vejl, & Soukup, 2014). Images of the pollen tube elongation raising pistils in the varieties 'Lapins'…”
Section: Pollination and Pollen Tube Growth Assayssupporting
confidence: 60%
See 1 more Smart Citation
“…Normal pollen tube growth was observed in varieties 'Lapins' and 'Staccato,' which agreed with their self-compatible S4 0 haplotype (Schuster, 2012;Sharma, Sedl ak, Zeka, Vejl, & Soukup, 2014). Images of the pollen tube elongation raising pistils in the varieties 'Lapins'…”
Section: Pollination and Pollen Tube Growth Assayssupporting
confidence: 60%
“… S ‐allele genotypes previously reported for varieties, incompatibility groups and origin were included. (1) Bošković & Tobutt, ; (2) Choi, Tao, & Anderson, ; (3) Hauck, Iezzoni, Yamane, & Tao, ; (4) Lacis, Kaufman, Rashal, Trajkovski, & Iezzoni, ; (5) Schuster, ; (6) Schuster, Flachowsky, & Köhler, ; (7) Sharma et al., ; (8) Sonneveld et al., ; (9) Sonneveld et al., ; (10) Tao et al., ; (11) Wiersma et al., ; (12) Wünsch & Hormaza, . SI, self‐incompatible; SC, self‐compatible; O, universal donor.…”
Section: Methodsmentioning
confidence: 99%
“…To identify the molecular mechanism underlying fruit skin colour in sweet cherry, we constructed an F1 population. Because Prunus avium exhibits gametophytic self-incompatibility, the dark-red variety 'Lapins' and the dark-red variety 'Wanhongzhu' were selected as cross-parents (Sharma et al, 2014). Analyses of the F1 hybrids showed that the 415 dark-red and 150 blush fruit skin phenotypes segregated in a 3 : 1 ratio.…”
Section: Mapping Identification and Analysis Of The R2r3-myb Tf Genesmentioning
confidence: 99%
“…The S-RNase play an important role in GSI, which is necessary and sufficient for pollen recognition [ 23 ]. Lots of S-RNase have been isolated in Rosaceae, such as: Malus pumila [ 24 ], Pyrus serotina [ 25 ], Prunus avium [ 26 ], Prunus dulcis [ 27 ], Prunus salicina [ 28 ], Eriobotrya japonica [ 29 ] and Prunus armeniaca [ 30 ]. We found a highly expressed gene (PRUPE_ppa018459mg) in ‘Liuyefeitao’ which is homologous to the S-RNase gene of Prunus dulcis ( S2 Table ).…”
Section: Discussionmentioning
confidence: 99%